APLIKASI PENETAPAN DISKON DALAM PELUNASAN MURABAHAH DI PERBANKAN SYARIAH - Yenti Afrida (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2015)
Implementing the Discount rate to settle Murabahah debt at Syariah Banking. This paperanalyzing the discount system determined by shariah bank in settling the murabahah debt before thedeadline. This paper were made in demand of sharia bank customers who felt disappoint when theywanted to settle the murabahah debt before the deadline, because the customers have to pay all theresidue of basic debt and residue of margin, but in some case the bank provide discount rate accordingto the bank provision. This system caused a burden to customers and many customers compare thesharia bank system with the conventional bank where in conventional bank the customers will begiven a penalty of one time interest rate. After a deep analysis the writer came to a conclusion that thedecision of discount rate in sharia bank is approppriate with the instruction of DSN MUI Number :23/DSN-MUI/III/2002 related to the discount rate for settling the murabahah debt before the deadline.It mentioned that “If the customer of murabahah settle the debt earlier or before the time as perprevious agreement, the financial institution may provide a discount from the obligation of paymentbut it must not be mentioned during the previous agreement.” The amount of discount is considereddepending on the provision of the Sharia Financial Institutions